Comparative analysis of the main reliability indices and parameters of two-stage thermoelectric devices with different geometry of the branches of thermoelements in various operating modes - Zaikov, V. P.; Meshcheryakov, V. I.; Zhuravlyov, Yu. I. (Technology and design in electronic equipment, 2017)
The paper presents a comparative analysis of the main parameters and reliability indices of two-stage thermoelectric devices with a variation in the geometry of the branches of thermoelements in cascades and temperature drops for characteristic current operating modes under the condition of identical configuration of branches in cascades. The authors propose criteria that allow building two-stage high-reliability thermoelectric devices choosing the current operation mode for a given geometry of the branches of thermoelements in cascades, considering the significance of each of the limiting factors.